Analysis energy production design from grid connected 40 MW large PV power plant - Moe, Khin Moe; Thar, Hla Aye; Aung, Hla Myo; Win, Yee Yee (Teknomekanik, 2023)
Electricity is an important source of energy in everyday life. In recent decades, growing energy demand worldwide has significantly fueled energy production, leading to environmental impacts such as global warming and ozone depletion. it has also endangered the species. Hence, the whole world has started shifting towards green energy generation, eliminating all the negative impacts on the environment. Solar energy is the most CO2 emission save compared to non-renewable energy sources. A photovoltaic generator is useful in areas well exposed to the sun. This paper is aimed the total amount of energy generated by the solar system connected to the grid on the 230 kV transmission line. This result was conducted by comparing the energy generated with tilt angle of 15°,20°,25°,30°and 35°. The most energy generated is produced with 25° of tilt angle according to the simulation result in this paper. The result was simulated by using PVsyst. This paper presents energy production of a 40-MW grid connected photovoltaic system located at Minbu Township in Myanmar. The simulation is carried out in order to get maximum energy production and the incident radiation, performance ratio, energy into the grid and energy output at array and losses. Based on the simulation result, it is concluded that maximum energy production and performance ratio are 75730 MWh and 81% through the year. The CO2 emission was saved 424781.5 tons per year. The incident energy in collector plane is 5.220kWh/m2/day. This research is only conducted for analysis on existing grid connected utility scale solar PV system and not provided for advanced techniques.